Perancangan Aplikasi Mobile Sistem Informasi Akademik Mahasiswa Sebagai Salah Satu Tahapan Metode DevOps - Wibowo, Satrio Muslim; Susanti, Erma; Fatkhiyah, Erfanti (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The student service information system is important for processing information at an educational institution. IST AKPRIND campus has implemented information services using mobile devices. In student information services, there is some information about lectures, such as study result cards, course schedules, student profiles, and student attendance. However, there are still areas for improvement in application, such as the lack of academic features in the service. The solutions in this study in the form of additions, improvements, and updates include adding a dynamic announcement feature, improving the payment history feature, improving the scan feature on self-presence, adding features to display the cumulative assessment index, semester credit units taken, active student status and updating the display design. The DevOps approach is used by the system development method because it can reduce the time between software creation and operation without sacrificing software quality. This study aims to apply the DevOps method design phase to the development of student service applications. The following stage of development is built upon the outcomes of this design.